Choroidal morphologic and vascular features in patients with unilateral idiopathic epiretinal membranes: An optical coherence tomography analysis integrated with assessment of retinal layers - Wang, Xinglin; Yang, Jiarui; Wang, Changguan; Li, Xuemin (Frontiers in Medicine, 2023)
Integrated analysis of retinal and choroidal morphologic and vascular features is urgently needed to examine whether and how these two elements interact with each other, thus contributing to visual impairment in patients with idiopathic epiretinal membranes (iERMs). An observational retrospective study consisting of 181 patients diagnosed with unilateral iERM between August 2019 and July 2022 was carried out at Peking University Third Hospital. All patients underwent a standardized set of ophthalmologic examinations, including EDI-OCT and OCTA scanning, and were subsequently categorized into four stages according to current classification schemes based on their OCT findings. Altogether, 15 qualitative and quantitative parameters of both the retina (full-layer, inner and outer layers) and choroid were identified. The results revealed variations in the choroidal vascularity index (CVI) among different stages of iERMs (p<0.001) for the first time. Distributions of retinal parameters across four stages of iERMs were validated. Correlation analysis between choroidal and retinal parameters showed that the CVI was associated with both inner and outer retinal morphologic biomarkers. Functional damage to retinal integrity was determined to be a strong contributor to visual acuity reduction in iERMs. This study complemented our present understanding of posterior segment structural and vascular alterations in iERMs.